Manual técnico para la aplicación del régimen de tráfico postal y régimen de mensajería acelerada o courier Ecuador periodo 2023. - Correa Torres, Jonathan Rafael; Valencia Puga, Miller Adrian (Machala : Universidad Técnica de Machala, 2023)
The aim of this research is to define the application of the postal traffic and expedited courier or Courier regime in Ecuador, by means of a technical manual. This initiative arises in a context in which international trade and global connection are fundamental, and the rapid dissemination of products and services requires an efficient and precise customs administration. The methodology adopts a qualitative, descriptive approach, with the intention of describing the most important aspects, particularities and elements of the object of study. This will allow a detailed and comprehensive approach to the different aspects, particularities and essential elements related to postal and courier traffic in the Ecuadorian context. Through this approach, the aim is to analyses in detail the existing procedures, regulations and challenges in this area. This research will be carried out through the review of scientific literature in indexed journals, with the aim of finding out what procedures have to be followed to avoid problems of postal traffic and expedited courier services within the country. The aim of this research is to explain the procedures for the postal and courier traffic regime within the country, and in this way, to reach an adequate knowledge. It is expected to obtain quality information that contributes to the construction of new notions regarding the phenomenon addressed. The knowledge generated has the potential to influence informed decision-making and the formulation of effective policies that will benefit both the development of international trade and the economic growth of the country.
La presente investigación tiene el objetivo de definir la aplicación del régimen de tráfico postal y mensajería acelerada o Courier en el ecuador, mediante un manual técnico. Esta iniciativa surge en un contexto en el que el comercio internacional y la conexión global son fundamentales, la rápida difusión de productos y servicios requieren una administración aduanera eficaz y precisa. La metodología adopta un estudio con enfoque cualitativo, de tipo descriptivo, con la intención de describir los aspectos, particularidades y elementos más importantes del objeto de estudio. Esto permitirá abordar de manera detallada y comprensiva los diferentes aspectos, particularidades y elementos esenciales relacionados con el tráfico postal y el Courier en el contexto ecuatoriano. A través de este enfoque, se aspira a analizar minuciosamente los procedimientos, las regulaciones y los desafíos existentes en esta área. Esta investigación se llevará a cabo mediante la revisión de literatura científica alojada en revistas indexadas, con la finalidad de conocer cuáles son los procedimientos que se tienen que seguir para evitar problemas de tráfico postal y mensajería acelerada dentro del país. Con esta investigación, se busca explicar cuáles son los procedimientos para el régimen de tráfico postal y Courier dentro del país, y de esta manera, llegar a un conocimiento adecuado. Se espera obtener información de calidad que aporte a la construcción nuevas nociones respecto al fenómeno abordado. Ya que, el conocimiento generado tiene el potencial de influir en la toma de decisiones fundamentadas y en la formulación de políticas efectivas que beneficien tanto al desarrollo del comercio internacional como al crecimiento económico del país.
Keywords: COURIER; TRÁMITES; RÉGIMEN ADUANERO; TRÁFICO POSTAL